Removal of old adhered mortar from crushed concrete waste aggregate (CCWA) with different HCl molarities and its effect on CCWA properties - A.A, Alodaini; A. R. M, Ridzuan; M. A. M, Fauzi (International Journal of Engineering and Technology, 2019)
Removing old adhered mortar from crushed concrete waste aggregates (CCWAs) is essential to ensure the quality of the CCWA used in the production of new concrete. Pre-soaking the CCWA in hydrochloric acid (HCl) solution was reported as an effective technique for the removal of old adhered mortar. However, the data on the treatment of CCWAs with HCl failed to address the influence of HCl molarity on CCWA properties, such as the aggregate crush value, aggregate impact value, and water absorption, and the correlation between treatment variables, such as size of aggregate, time of submersion in HCl, CCWA microstructure, and HCl molarity. Fifteen specimens of CCWA were prepared. One specimen was of untreated CCWA and fourteen specimens were treated; each of these specimens were treated with different HCl molarities of 0.2, 0.5, 1.0, 2.0, 3.0, 4.0, 5.0, 6.0, 7.0, 8.0, 9.0 10.0, 11.0, and 12.8. Experimental data were analyzed with SPSS. A 500x digital microscope was used to examine the microstructure surface of the aggregate. Results showed a significant correlation between the HCl molarity and CCWA properties. A higher HCl molarity resulted in better quality of CCWA. Furthermore, the microscope test showed a similar microstructure surface of CCWA when treated with 12.8 HCl.Â Â Â